Endogenous monetary policy in macroeconomic models : the role of commitment, conservative central banker and optimal central bank contracts in the credibility of monetary policy - Alajääskö, Pekka (VATT-tutkimuksia, ISSN 0788-5008, 1996)
Abstract (1 s.). Summary (2 s.).
Keywords: Euroopan talous- ja rahaliitto : EMU; rahapolitiikka; keskuspankit